Foraging Behaviour of the Himalayan Honeybee (Apis cerana F.) on Flowers of Fagopyrum esculentum M. and its Impact on Grain Quality and Yield - Singh, Madhusudan Man (Ecoprint: An International Journal of Ecology, 2009)
This paper presents the findings of two studies - one conducted on foraging behaviour of Himalayan honeybee (Apis cerana F.) on flowering buckwheat (Fagopyrum esculentum Moench) in November 2001 to 2002 and another on its impact on the grain quality and yield increment of this crop conducted during 2000-2002 under different pollination treatments at Kirtipur, Kathmandu valley. Apis cerana bees started their foraging activities early in the morning (06.14 ± 0.004) and ceased late in the evening (17.28 ± 0.011). Total duration of foraging activity was 10:00 h and the average duration of foraging trip was 4.5 ± 0.14 min. Two peaks of foraging activities were observed between 08.30 to 10.30 (Peak I) and 11.30 to 13.30 O' clock (Peak II). The peak I period was the main foraging period and peak II was the second foraging period, both were very useful from the pollination point of view. After this, Apis cerana activity slowly diminished to a stand still at 17.30 pm. The time spent by Apis cerana on the buckwheat inflorescence at different hours of the day 09.00, 12.00, 15.00 O' clock showed longest (24 ± 3 min) in the morning and it decreased as the afternoon approached. This study revealed that Apis cerana bee pollination increased grain set in terms of the total number of grains per plant (169.76 ± 4.10), grain weight (33.03 ± 0.26 g) and grain yield (4.40 ± 0.12 g). It also increased the value of fertility (16.08 ± 0.21) and harvest index (35.32 ± 0.35) when compared with Control pollination/excluding all the insects (CP) and Open pollination (OP) treatment. This is mainly due to greater number of pollinators in the Bee pollination (BP) treatment, their longer duration of foraging and also due to superior pollinating efficiency of Apis cerana bees. Key words: Apis cerana, F. beekeeping, buckwheat, fertility, foraging, harvest index, pollination, Kathmandu valley. doi: 10.3126/eco.v15i0.1940 ECOPRINT 15: 37-46, 2008